Influence of water molecule coordination on the magnetic properties of polyamine copper dinitrate complexes - Guskos, N.; Glenis, S.; V. Likodimos; Typek, J.; Fuks, H.; Wabia, M.; Szymczak, R.; Lin, C.L.; Perkowska, T.A. (Journal of Applied Physics, 2003)
Influence of water molecule coordination on the magnetic properties of polyamine copper dinitrate complexes was studied. It was found that the magnetic coupling between Cu2+ ions strongly depends on the presence of water molecules in the crystal structure. Electron paramagnetic resonance (EPR) measurements showed considerable temperature dependence of the Lande′ splitting factors and resonance linewidths for both complexes at low temperatures.